2014
DOI: 10.1371/journal.pone.0092900
|View full text |Cite
|
Sign up to set email alerts
|

Over-Expression of a Rice Tau Class Glutathione S-Transferase Gene Improves Tolerance to Salinity and Oxidative Stresses in Arabidopsis

Abstract: Glutathione S-transferases (GSTs) are multifunctional proteins encoded by large gene family in plants, which play important role in cellular detoxification of several endobiotic and xenobiotic compounds. Previously, we suggested the diverse roles of rice GST gene family members in plant development and various stress responses based on their differential expression. In this study, we report the functional characterization of a rice tau class GST gene, OsGSTU4. OsGSTU4 fusion protein was found to be localized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
103
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 61 publications
8
103
0
Order By: Relevance
“…4b). Similar behavior of transgenic plants expressing transgenes have also been observed and reported earlier (Vivek et al 2013;Sharma et al 2014). Higher chlorophyll retention in transgenic plants indicated lesser damage in the chloroplast and thylakoid structure that may occur due to dehydration.…”
Section: Overexpression Of Aasmo1 In Tobacco and Analysis Of Transgensupporting
confidence: 84%
“…4b). Similar behavior of transgenic plants expressing transgenes have also been observed and reported earlier (Vivek et al 2013;Sharma et al 2014). Higher chlorophyll retention in transgenic plants indicated lesser damage in the chloroplast and thylakoid structure that may occur due to dehydration.…”
Section: Overexpression Of Aasmo1 In Tobacco and Analysis Of Transgensupporting
confidence: 84%
“…Likewise, GST gene family was analyzed through genome-wide analysis and 31 GST genes were found to be responsive to auxin and cytokinin and many of them showed differential expression under abiotic stress conditions ). The role of GST genes in mediating crosstalk between auxin and abiotic stress responses has also been reported (Smith et al 2003 ;Sharma et al 2014 ). In another study, the transcriptome analysis of AZF1 and AZF2 overexpression transgenic lines showed downregulation of many auxin-responsive genes during osmotic stress and ABA treatments (Kodaira et al 2011 ).…”
Section: Auxin and Abiotic Stress: A Functional Genomics Perspectivementioning
confidence: 72%
“…The overexpression of an auxin-responsive GST gene, OsGSTU4 , enhanced tolerance to salinity and oxidative stresses in transgenic Arabidopsis plants (Sharma et al 2014 ). In another genome-wide analysis of glutaredoxin (GRX) gene family, among the 48 members, at least 11 GRX genes exhibited differential expression pattern under different hormone treatments.…”
Section: Differential Expression Of Auxin-responsive Genes Under Abiomentioning
confidence: 99%
“…Likewise, GST gene family was analyzed through genome-wide analysis and 31 GST genes were found to be responsive to auxin and cytokinin and many of them showed differential expression under abiotic stress conditions ). The role of GST genes in mediating crosstalk between auxin and abiotic stress responses has also been reported Sharma et al 2014 ). In another study, the transcriptome analysis of AZF1 and AZF2 overexpression transgenic lines showed downregulation of many auxin-responsive genes during osmotic stress and ABA treatments (Kodaira et al 2011 ).…”
Section: Auxin and Abiotic Stress: A Functional Genomics Perspectivementioning
confidence: 78%